Uca cryptica Naderloo, Türkay & Chen, 2010 (Crustacea: Brachyura:Ocypodidae) is no longer cryptic - Michie, Laura A.; Cragg, Simon M.; Barnes, R. S. K.; Bennett, Wayne A. (Zootaxa, 2015)
Uca cryptica Naderloo, Türkay & Chen, 2010, was originally described from four male specimens found in museum collections without any information regarding the site of collection. We present the first recorded field observations of this species and new morphological features. Specimens were observed and collected in the Wakatobi National Park, on the island of Kaledupa, Sulawesi Tenggara, Indonesia. Colouration of both males and females is described and ecology and distribution are noted. Uca cryptica has been seen coexisting with nine other species; one of the highest recorded numbers of Uca species living in sympatry.